Evaluating the Shelf Life of Chilled Raw and Pasteurized Goat Milk: An Analysis of Physicochemical and Microbial Content - N. S. Ibrahim; N. A. Zahari; N. I. Shamsul Nizam (Indonesian Journal of Agricultural Research, 2024)
Goat milk offers a variety of health benefits. The objective of this study is to evaluate the influence of refrigerated storage on the quality of unprocessed and pasteurized goat milk within a defined timeframe. In addition, also analyzes the chemical and microbiological composition of both raw and pasteurized goat milk during refrigerated storage to assess its longevity. Goat milk samples were obtained from healthy Saanen female goats, aged 3-4 years, with a body condition score (BCS) ranging from 2 to 3. The samples were taken from UniSZA Pasir Akar farm in Besut, Terengganu, Malaysia. The milk samples were processed through pasteurization. Exactly 10 goats were meticulously chosen, with each goat yielding 1 liter of milk. The goats were segregated into two cohorts: one cohort for raw milk (n=5) and the other for pasteurized milk (n=5). Subsequently, the milk samples from both groups were subjected to chilling storage experimentation at the food technology laboratory of Universiti Sultan Zainal Abidin (UniSZA) in Besut. The milk samples (duplicates) were monitored for 42 days to assess their physical characteristics. The pasteurized goat milk samples were evaluated for milk composition (fat, solid non-fat, protein, and lactose) and microbial contents (TPC and EMB) from Week 0 to Week 6. The effect of shelf life, composition values, and bacterial growth were measured weekly, and the data were presented descriptively (SEM±STD) with paired T-Test as the statistical analysis, considering p<0.15 as a significant difference. The findings revealed a downward trajectory in the physical attributes and chemical makeup of both unprocessed and pasteurized goat milk throughout the storage duration, resulting in decreases in fat, solid non-fat, protein, and lactose. The microbiological investigation revealed increased microbial levels in both raw and pasteurized milk after two weeks. Nevertheless, there was a subsequent decrease in the number of microorganisms from week 3 to week 6, indicating a phase of natural bacterial decline caused by limited nutrients and competition among bacteria. The study emphasizes the significance of maintaining sustainability in dairy production and addressing food safety concerns. It is crucial for customers to be informed about the duration of safe consumption of pasteurized milk and the potential threat of bacterial growth during prolonged cold storage